2021
DOI: 10.1002/cphc.202100075
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Processes Involving 18‐Crown‐6‐Ether in Activated Noncovalent Complexes with Protonated Peptides

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…It is known that non-covalent complex reactions between 18C6 and peptide facilitated peptide sequencing after complex activation by collisions in argon or electron capture/ transfer. [29] Since covalently bound 4fb18C6 should produce the same effect after collisions with argon, our first goal was to select a group of peptides to test this hypothesis. A total of 23 peptides from six proteins with different amino acid compositions were selected according to their length and polarity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that non-covalent complex reactions between 18C6 and peptide facilitated peptide sequencing after complex activation by collisions in argon or electron capture/ transfer. [29] Since covalently bound 4fb18C6 should produce the same effect after collisions with argon, our first goal was to select a group of peptides to test this hypothesis. A total of 23 peptides from six proteins with different amino acid compositions were selected according to their length and polarity.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these studies have shown that CEs are able to change their binding site after electron transfer. [29] Based on these results, we performed a series of CID-MS experiments in positive ion mode with intact and derivatized peptides using ESI to investigate the effects of labelling the N-terminus of peptides with 4fb18C6 as a potential reagent for de novo sequencing. The derivatization reaction takes place between the formyl group of 4fb18C6 and the amino group of the peptide under slightly acidic conditions (pH 6).…”
Section: Introductionmentioning
confidence: 99%